2019
DOI: 10.1016/j.molliq.2019.111394
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of ions hydration using molecular modeling

Abstract: Ion hydration phenomena are of great interest in the fields of physics, chemistry, biology, geochemistry and environment. However, few studies using identical calculation methods to characterize the hydration properties of ions in water and in electrolytic systems are available. Hence, it is difficult to compare the hydration properties of ions when they come from different methods. The objective of this work is, therefore, to use a unique approach to compare the hydration properties of ions in pure water and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 82 publications
4
27
0
Order By: Relevance
“…As shown in Figure 5 f, perhaps this is due to the decreased chain–chain interactions that fail to be arranged in order, such as those in 1 in H 2 O, and form numerous spiny and fibril structures, as observed in Figure 5 a. The above results further confirm the effects of ion hydration, which modifies water molecules around the ions and plays a broad role in many natural processes, [23] especially because 2 and 3 , without hydration in the crystals, fail to display any special superstructures. Previous studies have revealed that slight adjustments to the water molecules, especially the three water molecules highlighted in Figure 5 g, are triggered by Na + , [24] which suggests that, in PBS, with Na + as the dominant cation, the trihydrol is undoubtedly modified by Na + .…”
Section: Resultssupporting
confidence: 64%
“…As shown in Figure 5 f, perhaps this is due to the decreased chain–chain interactions that fail to be arranged in order, such as those in 1 in H 2 O, and form numerous spiny and fibril structures, as observed in Figure 5 a. The above results further confirm the effects of ion hydration, which modifies water molecules around the ions and plays a broad role in many natural processes, [23] especially because 2 and 3 , without hydration in the crystals, fail to display any special superstructures. Previous studies have revealed that slight adjustments to the water molecules, especially the three water molecules highlighted in Figure 5 g, are triggered by Na + , [24] which suggests that, in PBS, with Na + as the dominant cation, the trihydrol is undoubtedly modified by Na + .…”
Section: Resultssupporting
confidence: 64%
“…In our previous works, the solute hydration properties (ions and saccharides) in pure water and in mixture were studied via a full geometry optimization using the DFT method [ 24 , 25 , 26 ]. First, the ion coordination number, CN , which is defined as the number of water molecules directly bonded to the central ion in its solvation first layer, was determined [ 25 ]. Then, the number of interactions between the cation and the oxygen, n inter S/C+ , defined as the number of oxygen belonging to the saccharide in direct interaction with the ion, was calculated [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Then, the number of interactions between the cation and the oxygen, n inter S/C+ , defined as the number of oxygen belonging to the saccharide in direct interaction with the ion, was calculated [ 26 ]. Results concerning the ion coordination number and the number of interactions between glucose and different cations are given in Table 5 [ 25 , 26 ]. In saccharide/cation/water systems, results showed that saccharides are all the more dehydrated as the number of saccharide/cation interactions increases, n inter S/C+ [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations